How Do We Evaluate the Good Test of Arabic in High School in Indonesia?/كيف نواصف الاختبار الجيد لمادة اللغة العربية في المدرسة الثانوية بإندونيسيا؟ - Eva Lathifah (JURNAL IJ-ATL, 2018)
The teaching process consists of four pillars: the teaching objectives, the needs and preparations of the students, the input of behavioral inputs, experiences or educational activities, and the measurement and evaluation. These four pillars are interconnected to each other organically so that one cant be dispensed with the other. Therefore, this research aims to know the calendar in general. The research also deals with the knowledge of the good test specifications in the Islamic schools, especially the secondary school, and the quality of the exam in the final exam in the academic year 2015/2016.إن العملية التدريسية تتكون من أربعة أركان وهي الأهداف التدريسية وحاجات واستعدادات التلاميذ المساة بالمدخلات السلوكية والخبرات أو الأنشطة التعليمية ثم  القياس والتقويم. وترتبط هذه الأركان الأربع بعضها ببعض ارتباطا عضويا بحيث لا يستغنى أحدها عن الأخر. لذا، يهدف هذا البحث إلى معرفة التقويم بوجه عام، كما يتطرق البحث إلى معرفة مواصفات الاختبار الجيد في المدارس الإسلامية بخاصة المدرسة الثانوية ومعرفة جودة الاختبار في الامتحان النهائى المقنن فيها للعام الدراسي 2015/2016 مـ.